High-resolution behavioral time series of Japanese quail within their social environment - Caliva, Jorge Martín (2019)
The behavioral dynamics within a social group not only could depend on individual traits and social-experience of each member, but more importantly, emerges from inter-individual interactions over time. Herein, we first present a dataset, as well as the corresponding original video recordings, of the results of 4 behavioral tests associated with fear and aggressive response performed on 106 Japanese quail. In a second stage, birds were housed with conspecifics that performed similarly in the behavioral tests in groups of 2 females and 1 male. By continuously monitoring each bird in these small social groups, we obtained time series of social and reproductive behavior, and high-resolution locomotor time series. This approach provides the opportunity to perform precise quantification of the temporal dynamics of behavior at an individual level within different social scenarios including when an individual showing continued aggressive behaviors is present. These unique datasets and videos are publicly available in Figshare and can be used in further analysis, or for comparison with existing or future data sets or mathematical models across different taxa.